Abundance of Ordo Lepidoptera in The Land Conversion of Ciwidey Pine Forest - Sabella Friska S. Mulyono; Suhara Suhara; Iwan Setia Kurniawan (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
The study entitled